Troponin Improves the Yield of Transthoracic Echocardiography in Ischemic Stroke Patients of Determined Stroke Subtype. Issue 11 (November 2018) - Yaghi, Shadi; Chang, Andrew D.; Cutting, Shawna; Jayaraman, Mahesh; McTaggart, Ryan A.; Ricci, Brittany A.; Dakay, Katarina; Narwal, Priya; Grory, Brian Mac; Burton, Tina; Reznik, Michael; Silver, Brian; et al.
Abstract : Background and Purpose—: Transthoracic echocardiography (TTE) is widely used in the ischemic stroke setting. In this study, we aim to investigate the yield of TTE in patients with ischemic stroke and known subtype and whether the admission troponin level improves the yield of TTE. Methods—: Data were abstracted from a single-center prospective ischemic stroke database for 18 months and included all patients with ischemic stroke whose etiologic subtype could be obtained without the need of TTE. Unadjusted and adjusted regression models were built to determine whether positive cardiac troponin levels (≥0.1 ng/mL) improve the yield of TTE, adjusting for demographic and clinical characteristics. Results—: We identified 578 patients who met the inclusion criteria. TTE changed clinical management in 64 patients (11.1%), but intracardiac thrombus was detected in only 4 patients (0.7%). In multivariable models, there was an association between TTE changing management and positive serum troponin level (adjusted odds ratio, 4.26; 95% CI, 2.17–8.34; P <0.001). Conclusions—: In patients with ischemic stroke, TTE might lead to a change in clinical management in ≈1 of 10 patients with known stroke subtype before TTE but changed acute treatment decisions in <1 percent of patients. Serum troponin levels improved the yield of TTE in these patients. Abstract : Supplemental Digital Content is available in the text.